2021
DOI: 10.1038/s41598-021-93550-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of aragonite mineralization with a chelating agent for CO2 storage and utilization at low to moderate temperatures

Abstract: Among the CaCO3 polymorphs, aragonite demonstrates a better performance as a filler material in the paper and plastic industries. Despite being ideal from the environmental protection perspective, the production of aragonite particles via CO2 mineralization of rocks is hindered by the difficulty in achieving high production efficiencies and purities, which, however, can be mitigated by exploiting the potential ability of chelating agents on metal ions extraction and carbonation controlling. Herein, chelating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 48 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…The preferred dissolution of plagioclase over clinopyroxene from basalt was consistent with the result of Nesbitt and Wilson (1992) (Nesbitt and Wilson, 1992). Calcite is the main product of basalt carbonation, as evidenced by the characteristic calcite peak at 29.6 °(2θ, CuKα) (Wang et al, 2021) after reaction of basalt in NaHCO 3 solution, and the calcite peak showed higher intensity when the reaction time increased from 5 to 10 days, suggesting an increase in calcite concentration in the reacted sample. Meanwhile, peaks of analcime (e.g., 15.8 °, 26.0 °), a Na-Al silicate with the general chemical formula of NaAlSi 2 O 6 •H₂O, and smectite (in the range of 6.3 °-8.0 °), a clay mineral contains Mg, Fe, Si, as well as Al (Yamashita et al, 2019), were also detected.…”
Section: Effects Of Nahco 3 As a Function Of Reaction Durationsupporting
confidence: 83%
See 1 more Smart Citation
“…The preferred dissolution of plagioclase over clinopyroxene from basalt was consistent with the result of Nesbitt and Wilson (1992) (Nesbitt and Wilson, 1992). Calcite is the main product of basalt carbonation, as evidenced by the characteristic calcite peak at 29.6 °(2θ, CuKα) (Wang et al, 2021) after reaction of basalt in NaHCO 3 solution, and the calcite peak showed higher intensity when the reaction time increased from 5 to 10 days, suggesting an increase in calcite concentration in the reacted sample. Meanwhile, peaks of analcime (e.g., 15.8 °, 26.0 °), a Na-Al silicate with the general chemical formula of NaAlSi 2 O 6 •H₂O, and smectite (in the range of 6.3 °-8.0 °), a clay mineral contains Mg, Fe, Si, as well as Al (Yamashita et al, 2019), were also detected.…”
Section: Effects Of Nahco 3 As a Function Of Reaction Durationsupporting
confidence: 83%
“…The urgent need to reduce the amount of carbon dioxide (CO 2 ) for creating a carbon neutral society has driven the development of various CO 2 capture, utilization, and storage (CCUS) techniques (Voigt et al, 2021). Among the CCUS techniques, mineralization of CO 2 to water-insoluble carbonates using Mg or Ca-rich rocks such as basalt (Goldberg et al, 2008;Okoko and Olaka, 2021), peridotite (Oelkers et al, 2008) and wollastonite (Wang et al, 2021) is a promising method for large-scale and long-term CO 2 storage with low risk of releasing stored CO 2 into the atmosphere (Zhao et al, 2015) and probably a relative acceptable cost (National Academies of Sciences, 2018; Kelemen et al, 2019). Basalt is one of the optimum rocks for CO 2 storage because of its chemical composition, abundant distribution and easy availability.…”
Section: Introductionmentioning
confidence: 99%
“…However, Ethylenediaminetetraacetic acid (EDTA) is widely used in several applications, and its persistence in aquatic systems is leading to serious environmental consequences. GLDA salts are biodegradable candidates that can replace EDTA [30,31]. They showed a strong capability of chelating calcium ions at pH values in a certain range [32,33].…”
Section: Introductionmentioning
confidence: 99%